The Hong Kong government's role in the SAR's future after China's WTO accession. - Chu, William Tai Hong. (2008)
This study starts with a question: "How may the special administrative region (SAR) government play a role in preventing Hong Kong from losing her economic significance following China's recession to the WTO?" and proceeds with a quanlitative case study approach, focusing on the broad macro strategic issues to the Hong Kong economy.